2011
DOI: 10.5047/eps.2011.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of M w 9.0 mainshock triggered by diffusional propagation of after-slip from M w 7.3 foreshock

Abstract: For the 2011 off the Pacific coast of Tohoku, Japan, Earthquake, we have investigated the spatio-temporal changes in seismicity from the M w 7.3 foreshock, March 9, 2011, 11:45, to the M w 9.0 mainshock, March 11, 14:46 (Japan Standard Time). We found that seismic activities slowly migrated from the source area of the foreshock, which presumably reflected the propagation of the after-slip. The mainshock rupture was initiated when the migration reached the hypocentral location of the mainshock. We also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 20 publications
(23 reference statements)
6
66
0
Order By: Relevance
“…7(d)). This result supports early studies on foreshock migration based on the onshore stations (Ando and Imanishi, 2011;Kato et al, 2012). Those works had pointed out that the foreshock activity migrated toward the MS, presumably as a result of diffusional propagation of the LSF afterslip.…”
Section: Foreshock Seismicity Near the Mainshock Hypocen-supporting
confidence: 90%
See 1 more Smart Citation
“…7(d)). This result supports early studies on foreshock migration based on the onshore stations (Ando and Imanishi, 2011;Kato et al, 2012). Those works had pointed out that the foreshock activity migrated toward the MS, presumably as a result of diffusional propagation of the LSF afterslip.…”
Section: Foreshock Seismicity Near the Mainshock Hypocen-supporting
confidence: 90%
“…In this paper, we refer to the earthquakes that preceded the M-9 earthquake as foreshocks of the Tohokuoki earthquake because of their proximity to the Tohokuoki earthquake in terms of time and space. Further, from the hypocenter catalogue published by JMA, it has been pointed out that the epicenters of the foreshocks migrated toward the hypocenter of the mainshock of the Tohoku-oki earthquake (Ando and Imanishi, 2011;Kato et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on spatial change of seismicity include the following papers. Ando and Imanishi (2011) investigated the seismicity between the M W 7.3 earthquake on March 9, 2011 (foreshock) and the M W 9.0 Tohoku-oki earthquake on March 11, 2011. They found that hypocenters appeared to migrate toward the M W 9.0 earthquake and proposed the possibility that these earthquakes were triggered by diffusional propagation of afterslip from the M W 7.3 foreshock.…”
Section: Studies On Seismicity and Stress Dropmentioning
confidence: 99%
“…8), induced by the M w 5.7 earthquake rather than either pre-seismic anomalies or the oceanic noise, which also has two dominant peaks at 5 -6 and 10 -15 s (Longuet-Higgins 1950;Hinderer et al 2007). The fluctuations are neither likely response to the accelerating process nor foreshocks before the M w 9.0 earthquake (Ando and Imanishi 2011;Kato and Yoshida 2011;Kennett et al 2011;Kato et al 2012;Tajima et al 2013). Most foreshocks have magnitudes larger than M w 5.7 and they would have influenced the gravity observations and thus need to be removed from the source detection for gravity signals with frequencies of 0.10 -0.20 Hz.…”
Section: Discussionmentioning
confidence: 99%